Biocontrol of plant Pathogen Phellinus Noxius by selected actinomycetes, bacteria and fungi / Prof Madya Dr. Zainon Mohd Noor - Mohd Noor, Zainon (Research Management Institute (RMI), 2011)
The Phellinus noxius which are the plant pathogen caused brown root rot disease and harmful to the plantation industry. In Malaysia, disease was found in teak plantations in Selangor, Perak, Kedah and Melaka. A study was conducted to evaluate the antagonistic activities of selected fungal and bacterial species which included P. aeruginosa, B.subtilis, Trichoderma spp. TT1 actinomycete y TT2 actinomycete and TT3 actinomycete towards the plant pathogens. All the antagonists were found to have antagonistic activities against the fungal pathogens when evaluated by the dual culture assay on potato dextrose agar (PDA) and ISP-2 at 30°C. The Trichoderma spp. is the best antagonist due to the highest percentage inhibition ranging from 14.28% to 100%. There are 3 mechanisms of antagonisms has been done such as competitive inhibition, mycoparatism or antibiosis. For competitive inhibition, Trichoderma spp. showed the fastest growth which indicated it to be very competitive to the pathogens for the substrates, nutrients and space. Meanwhile mycoparasitic interactions were investigated by using light microscopy and scanning electron microscopy. Under the microscopic observations showed that the hyphae of Phellinus noxius shrink, swell and become stunt. Activity of chitinolytic enzymes was detected when the antagonists formed clearing zone chitin yeast extract agar and only TT1 and TT3 actinomycete strains was produced a positive results with the significant clear zone (> 0.5cm of diameter). Activity of cellulolytic enzymes was detected when the antagonists formed halos on CMC plate assay and the highest secretion was showed by TT2 actinomycete with the halo diameter was 1.40cm. Under the antibiosis using cell-free culture filtrate by agar well diffusion bioassay, all antagonuists effectively against plant pathogen except TT1 actinomycete was not effective against Phellinus noxius due to the absence of inhibition zone. During the antibiosis using solvent extracts methanol extract gave a positive result. The methanol extract of P. aeruginosa produced the widest zone of inhibition among other antagonists.